2014
DOI: 10.1055/s-0034-1367730
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Cryotherapy Use in Anterior Cruciate Ligament Reconstruction

Abstract: Unrelieved postoperative pain may impair rehabilitation, compromise functional outcomes, and lead to patient dissatisfaction. Preemptive multimodal analgesic techniques may improve outcomes after surgery. We hypothesized that patients using preoperative cryotherapy plus a standardized postoperative treatment plan will have lower pain scores and require less pain medication compared with patients receiving a standardized postoperative treatment plan alone after arthroscopically assisted anterior cruciate ligame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 9 publications
(10 reference statements)
0
7
0
Order By: Relevance
“…This evidence is consistent with previous literature that has deemed bracing to have no beneficial effects 62 . Both preoperative 18 and postoperative 19 uses of cryotherapy were effective at reducing pain perception, and preoperative use also reduced painkiller consumption 18 . Various types of intraoperative analgesia were investigated for their effects on postoperative pain scores and muscular function; periarticular injections were found to yield significantly better pain scores 32 , and both femoral nerve blocks and adductor canal blocks did not lead to any significant differences in long-term quadriceps muscular function 30,31 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This evidence is consistent with previous literature that has deemed bracing to have no beneficial effects 62 . Both preoperative 18 and postoperative 19 uses of cryotherapy were effective at reducing pain perception, and preoperative use also reduced painkiller consumption 18 . Various types of intraoperative analgesia were investigated for their effects on postoperative pain scores and muscular function; periarticular injections were found to yield significantly better pain scores 32 , and both femoral nerve blocks and adductor canal blocks did not lead to any significant differences in long-term quadriceps muscular function 30,31 .…”
Section: Discussionmentioning
confidence: 95%
“…Cryotherapy includes the use of cold packs, ice massage, cold baths, vapocoolant sprays, and cold compression units and is an analgesic technique used to relieve muscular soreness following musculoskeletal injury 17 . Two studies were included that investigated the use of cold therapy as an analgesic for populations undergoing ACL reconstruction 18,19 (Table V). The results provided further evidence to support the use of cryotherapy both preoperatively 18 and postoperatively 19 as an analgesic for patients in ACL reconstruction (Table I).…”
Section: Resultsmentioning
confidence: 99%
“…Some data suggest that cryotherapy and cold application reduces edema around the knee by reducing vasodilation after TKA [18,19]. Moreover, Ruffilli et al evaluated knee circumference and found no significant postoperative difference in the measurements of 15 upper and lower patella regions [16].…”
Section: Discussionmentioning
confidence: 99%
“…They found no negative effect of cold therapy on knee stability after studying tibial translation. In 2014, Koyonos et al 19 questioned the indication for intraoperative cryotherapy and found a significative reduction in pain and analgesic intake. Several studies also showed the advantage of compressive therapy combined with cryotherapy.…”
Section: Discussionmentioning
confidence: 99%